The Role of Local Food in Improving the Nutritional Status of the Community in Purwosari Village, Nagan Raya Regency - Maiza Duana; Fikri Faidul Jihad; Safrida; Cut Mega Putri; Rahma Hidayati; Ambia Nurdin; Muhammad Furqan; Amiruddin; Yulizar Kasma (Mitra Akademia Indonesia, 2026)
Nutritional problems, particularly stunting, remain a serious challenge in Indonesia, including in Aceh Province, which ranks fifth in the highest stunting prevalence nationally. One of the contributing factors is the suboptimal utilization of local food resources that actually have high nutritional potential and are easily accessible to the community. This community service activity aims to increase the knowledge and awareness of the people of Purwosari Village, Nagan Raya Regency, regarding the importance of utilizing local food as an effort to improve family nutrition, especially for preventing stunting in children. The implementation method used a qualitative approach through nutrition education, demonstrations of processing nutritious local foods, and interactive discussions with the community. The results of the activity showed an increase in community understanding of the concept of balanced nutrition, the importance of animal protein for children's growth and development, and proper methods of processing local food. In addition, innovations in local food products such as modified cassava flour (mocaf) and grilled eggplant with fish-based dishes received positive responses as opportunities for small-scale family businesses. This activity is in line with the theory of local food security and previous studies emphasizing the role of local food in improving the nutritional status of rural communities. Therefore, optimizing the use of local food can be an effective strategy in supporting food security and reducing stunting rates in rural areas.